Chiral Separation of Benzothiazole Derivatives of Amino Acids using Capillary Zone Electrophoresis - Nováková, Zuzana; Pejchal, Vladimír; Fischer, Jan; Česla, Petr (My University, 2017)
A method for the separation of enantiomers of leucine and phenylalanine benzothiazole derivatives as potential antimicrobial agents was developed using capillary zone electrophoresis with a dual cyclodextrin system. The best resolution of enantiomers was achieved in 100 mmol/L phosphate background electrolyte pH 3.5 with dual cyclodextrin system consisting of 10 mmol/L of beta-cyclodextrin with 10 mmol/L of 2-hydroxypropyl-beta-cyclodextrin for leucine derivative and 10 mmol/L of 2-hydroxypropyl-gamma-cyclodextrin for phenylalanine derivative, respectively. Under the optimal conditions, highest enantioresolution 1.25 was achieved in a non-coated fused silica capillary at 17°C and 24 kV applied voltage.
Chirální separace benzthiazolových derivátů aminokyselin pomocí kapilární zónové elektroforézy
Keywords: amino acids; benzothiazole derivatives; capillary zone electrophoresis; dual cyclodextrin system; polydimethylacrylamide-coated capillaries; aminokyseliny; benzthiazolové deriváty; kapilární zónová elektroforéza; duální cyklodextrinový systém; kapiláry pokryté polydimethylakrylamidem